Gambaran Gingivitis Pada Perokok Pemuda Usia Remaja Dan Dewasa di Asrama Persatuan Mahasiswa Wacuata Kota Makassar - Feblina, Ayu Rahayu; Rapiuddin, Risman Abdi; Ikmaluddin, Ikmaluddin (Barongko: Jurnal Ilmu Kesehatan, 2024)
Introduction: Gingivitis is a periodontal tissue disease, namely the gingival margin is reddish to bluish red, enlarged gingival contour due to edema and easy bleeding. This is caused by poor dental and oral hygiene indicators. Characterized by plaque and tartar. Plaque that is left and not cleaned will become thicker and within an hour will form a pellicle, a mucous membrane from saliva that covers the teeth. The longer the plaque is not cleaned, it causes the gingival edge to be reddish to bluish red and enlargement of the gingival contour due to edema and easy bleeding.Research method: This study uses a descriptive method where the sample is 34 people, to conduct a direct examination, a set of diagnostic tools, observation sheets, and a list of questions are used for each sample, after data collection is carried out, the data is processed and analyzed, this study was conducted at the Wacuata Student Association Dormitory, Makassar City in 2024.Research results: From the results of data processing, it was obtained that gingivitis gingivitis with moderate criteria was 20 people (59%), and mild criteria were 12 people (35%) and severe criteria were 2 people (6%).Conclusion: In conclusion, the level of dental and oral hygiene can cause gingivitis caused by smoking in Youth at the Wacuata Student Association Dormitory, Makassar City.